2011
DOI: 10.1017/s1461145711000149
|View full text |Cite
|
Sign up to set email alerts
|

Increased NF-κB signalling up-regulates BACE1 expression and its therapeutic potential in Alzheimer's disease

Abstract: Elevated levels of β-site APP cleaving enzyme 1 (BACE1) were found in the brain of some sporadic Alzheimer's disease (AD) patients; however, the underlying mechanism is unknown. BACE1 cleaves β-amyloid precursor protein (APP) to generate amyloid β protein (Aβ), a central component of neuritic plaques in AD brains. Nuclear factor-kappa B (NF-κB) signalling plays an important role in gene regulation and is implicated in inflammation, oxidative stress and apoptosis. In this report we found that both BACE1 and NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
294
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 343 publications
(299 citation statements)
references
References 41 publications
5
294
0
Order By: Relevance
“…Multiple mechanisms are recently proposed to mediate the upregulation of BACE1 associated with AD. Those include the increased phosphorylation of the translation initiation factor eIF2a Devi and Ohno, 2010b;O'Connor et al, 2008), caspase-3-dependent inactivation of GGA3 leading to decreased lysosomal degradation of BACE1 (Sarajarvi et al, 2009;Tesco et al, 2007), changes in microRNA expression profiles (Hebert et al, 2008;Wang et al, 2008), p25/cyclin-dependent kinase 5 pathways (Cruz et al, 2006;Wen et al, 2008), calpain activation (Liang et al, 2010), the receptor for advanced glycation end products (RAGE) (Cho et al, 2009;Guglielmotto et al, 2010), and oxidative stress or related signals such as nuclear factor-kB, c-Jun N-terminal kinase, and p38 MAPK (Chen et al, 2011;Chen et al, 2008;Coma et al, 2008;Xiong et al, 2007). Further study will be needed to determine the molecular pathways by which activation of BDNF-TrkB signaling may counteract the BACE1 elevation in 5XFAD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms are recently proposed to mediate the upregulation of BACE1 associated with AD. Those include the increased phosphorylation of the translation initiation factor eIF2a Devi and Ohno, 2010b;O'Connor et al, 2008), caspase-3-dependent inactivation of GGA3 leading to decreased lysosomal degradation of BACE1 (Sarajarvi et al, 2009;Tesco et al, 2007), changes in microRNA expression profiles (Hebert et al, 2008;Wang et al, 2008), p25/cyclin-dependent kinase 5 pathways (Cruz et al, 2006;Wen et al, 2008), calpain activation (Liang et al, 2010), the receptor for advanced glycation end products (RAGE) (Cho et al, 2009;Guglielmotto et al, 2010), and oxidative stress or related signals such as nuclear factor-kB, c-Jun N-terminal kinase, and p38 MAPK (Chen et al, 2011;Chen et al, 2008;Coma et al, 2008;Xiong et al, 2007). Further study will be needed to determine the molecular pathways by which activation of BDNF-TrkB signaling may counteract the BACE1 elevation in 5XFAD mice.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a G/C polymorphism in exon 5 of the BACE1 gene might be associated with some sporadic cases of AD (17)(18)(19). Although genetic analyses from our and other laboratories have failed to uncover any mutation in the BACE1 coding sequence or any diseaseassociated SNP in its promoter region in AD patients (20)(21)(22), increased β-secretase levels and activity have been reported in AD (23)(24)(25)(26)(27). BACE1 levels were elevated in neurons around plaques (28).…”
Section: Introductionmentioning
confidence: 94%
“…We reported that hypoxia, a common vascular component among AD risk factors, increased BACE1 expression, resulting in both increased Aβ deposition and memory deficits in AD transgenic mice (30). Recently we found that both NF-κB and BACE1 levels were increased in sporadic AD patients, and NF-κB facilitated BACE1 gene expression and APP processing (27). Thus, increased BACE1 expression by NF-κB signaling in the brain could be one of the mechanisms underlying AD development (27).…”
Section: Introductionmentioning
confidence: 99%
“…As the population of the 3 European continent continues to age, it is predicted that AD will continue to be a 4 major public health problem. Consequently, there is need to identify and develop 5 therapeutic strategies aimed at delaying progression of AD. 6 Neurodegeneration in AD is linked to the accumulation of senile plaques which 7 consist of small peptides, known as amyloid-β (Aβ), and intracellular neurofibrillary 8 tangles, consisting of aggregates of hyperphosphorylated tau protein [3].…”
mentioning
confidence: 99%
“…6 Neurodegeneration in AD is linked to the accumulation of senile plaques which 7 consist of small peptides, known as amyloid-β (Aβ), and intracellular neurofibrillary 8 tangles, consisting of aggregates of hyperphosphorylated tau protein [3]. 9 Neuroinflammation is a process which principally involves activation of astrocytes 10 and microglia by inflammatory mediators in AD [4,5]. However, in spite of the widely- 11 reported roles of microglia and astrocytes in neuroinflammation, it has been 12 suggested that PGE2 produced in neurons may contribute to the self-propagating 13 processes involved in AD.…”
mentioning
confidence: 99%